Diverse sources for endocrine disruption in the wild. (1st January 2016) - Lambert, Max R.; Skelly, David K.
ABSTRACT: We are increasingly realizing that diverse human activities are associated with endocrine disruption in wildlife populations. Most field research on endocrine disruption tends to narrowly target particular endocrine disrupting chemicals (EDCs) and contaminant sources as the dominant culprit of observed endocrine disruption. Recently, we and our colleagues assessed patterns of endocrine disruption in metamorphosing frogs in ponds along a forest-suburban land use gradient. In conjunction, we assayed for a diversity of putative of EDCs from an array of possible sources. We found that endocrine disruption in suburban frog populations was associated with a cocktail of different EDCs including classical estrogens, phytoestrogens, and metalloestrogens. These results indicate that endocrine disruption in suburban frogs is likely to be the product of multiple chemicals and sources. Our findings have implications for other systems where endocrine disruption is attributed to a limited set of contaminants or sources without necessarily exploring the contributions of other EDC pathways. Here, we discuss our findings in the context of other field endocrine disruption research and encourage future studies to assess the broader EDC landscape which may be impacting wildlife populations.